Commodities and Development Report 2019 - United Nations Conference on Trade; Development (United Nations, 2019)
This report explores key aspects of the two-way relationship between commodities and climate change, discusses the concept of natural resource conversion and explores its application to renewable and non-renewable resources. In addition, it analyses the challenges and opportunities posed by climate change and the Paris Agreement to commodity-dependent developing countries, and discusses commodity-sector strategies in a changing climate. The report concludes with policy recommendations.